Predetermined participation: Social workers evaluating children's agency in domestic violence interventions. (May 2014) - Iversen, Clara
This article examines how ideals of children's participation and model consistency compete in social workers' accounts of intervention outcomes in 35 evaluation interviews in Sweden. Using discursive psychology, the analysis demonstrates how the social workers rely on category-based accounts: They describe willing children as competent, unwilling children as developing, and children attempting to rule in counselling as problematic. The interviews' focus on following the intervention model constructs a limited, predetermined participation that only respects children's wishes when they agree with the intervention. In showing this, the study contributes to further understanding of tensions between the principle and practice of participation.